Dreams and visions in the early Middle Ages the reception and use of patristic ideas, 400-900 - Keskiaho, Jesse 1979- (New York Cambridge University Press, 2015)
Dreams and visions played important roles in the Christian cultures of the early middle ages. But not only did tradition and authoritative texts teach that some dreams were divine, some also pointed out that this was not always the case.
1. Introduction; 2. Dreams in hagiography and other narratives; 3. Dreams and apparitions. Patristic ideas and their reception; 4. The epistemology of visions. The reception of Augustine on the three visiones; Conclusion; Epilogue. Dreams and visions in early medieval thought; Appendix 1. The pre-tenth-century manuscripts of the main works discussed; Bibliography; Index.
Keywords: Dreams -- Religious aspects -- Christianity; Church history -- Primitive and early church, ca. 30-600.; Church history -- Middle Ages, 600-1500.